Favourable effects of whey protein on acetic acid-induced ulcerative colitis in a rat model - Tunc, Nurettin; Sahin, Abdurahman; Demirel, Ulvi; Artas, Gokhan; Şahin, Kazım; Bahcecioglu, Ibrahim Halil; Yalniz, Mehmet (Termedia Publishing House Ltd, 2022)
Introduction: In the present study, we aimed to examine the effects of the administration of whey protein through rectal enema to rats with acetic acid-induced ulcerative colitis on the pathways of nuclear-related factor-2 (Nrf-2), haem oxygenase-1 (HO-1), nuclear factor KB (NF-KB), active protein kinase-1 (AP-1), tumour necrotising factor-alpha (TNF-alpha), and cyclooxygenase-2 (COX-2), IL-6, IL-10.Material and methods: Twenty-eight rats were employed for the trial. Ul-cerative colitis was induced through the use of acetic acid. The therapeutic doses of whey protein were administered rectally. Ulcerative colitis was sub-jected to histopathological examination and protein levels in colon tissue were measured with the Western blot method.Results: The significant increases observed in the levels of AP-1, COX-2, IL-6, IL-10, NF-KB, and TNF-alpha as markers of inflammation following the devel-opment of ulcerative colitis showed remarkable decreases along with the administration of whey protein (p < 0.05). On the other hand, we identified a decrease in the Nrf2-ARE signal pathway and HO-1 protein having protec-tive roles in the colon inflammatory response along with the development of ulcerative colitis and activation of the Nrf2-HO-1 pathway by the whey protein. Conclusions: Whey protein modulates Nrf2/HO-1 and NF-kB pathways, thereby creating a therapeutic effect against colonic inflammation induced by acetic acid (AA) due to its anti-inflammatory effects.
Keywords: whey protein; Nrf2; HO-1; NF-KB pathway; acetic acid-induced ulcerative colitis